Analysis of Assembly Tolerance Based on Assembly Constraint Information Model. (9th August 2021) - Li, Chunxi; Hou, Wenjun
Abstract : Mechanical products are composed of two or more parts. The geometric tolerance and dimensional tolerance of each feature in part will affect the assembly performance of the product, which are accumulated and propagated between assembly fit and parts. In this paper, through the secondary development of CAD software, the B-rep model of parts is obtained. The model information is decomposed and simplified based on geometric features to obtain the key information of parts in the assembly process, simplify the operation, and improve the accuracy. Through a directed graph network, the transmission model of assembly error information based on geometrical and dimensional tolerances (GD&T) on the surface of parts is established. Combined with the error transfer characteristics of different geometric surfaces and different error sources, guided by the breadth-first search algorithm and the shortest path theory, the search and establishment of a three-dimensional assembly chain are realized. Finally, the three-dimensional chain is simulated by the Monte Carlo method. The calculation results are compared with the error range obtained by the traditional method to prove the effectiveness of the method.